Upaya Pengembangan TWA Lau Debuk Debuk Berbasis Masyarakat Effort Development of TWA Lau Debuk Debuk base on Society. - Afriyanti Br Sembiring; Pindi Patana; Agus Purwoko (Peronema Forestry Science Journal, 2012)
AFRIYANTI SEMBIRING. Effort Development of TWA Lau Debuk Debuk base on Society. Under supervised by Pindi Patana and Agus Purwoko. This study is aimed to know benefit and potency of TWA Lau Debuk Debuk, knowing role and perception and also society in development of TWA Lau Debuk Debuk and also formulate strategy alternative of society in developing TWA Lau Debuk Debuk. This research was conducted with purposive sampling method, while analysis method used descriptive analysis. Result of research indicates that the level of community participation in the activity of development TWA Lau Debuk Debuk is in the middle category where is society seldom to follow the activity. The Important Factor which determine efficacy of development of TWA Lau Debuk Debuk is participation of society like planning, execution, and program evaluation development of TWA Lau Debuk Debuk. Keyword: Ecotourism,  participation of society, TWA Lau Debuk Debuk.